Ecological efficiency of production and the ecological footprint of organic agriculture - Turinek, Matjaž; Turinek, Maja; Grobelnik Mlakar, Silva; Bavec, Franc; Bavec , Martina (Journal for Geography, 2010)
The rising energy prices and climatic changes have intensified the search for alternative farming systems where energy consumption per unit would be lowered. A long-term field trial, started in 2007 at the University of Maribor, focuses on food quality and the ecological footprint of conventional (CON), integrated (INT), organic (ORG) and biodynamic (BD) farming systems. The gained data has been evaluated and interpreted using the SPIonExcel tool. Results from the first year show better environmental performance of both, ORG and BD systems in production of wheat (Triticum aestivum L.) and spelt (Triticum spelta L.), mainly due to the non-use of external synthetic production factors. When yields are added to the equation, the ORG and BD systems emerge also as more efficient per unit of land area. Thus, the ORG and BD farming systems present viable alternatives for reducing the impact of agriculture on climate change, while ensuring a more sustainable food security.